On Topological Indices of Total Graph and Its Line Graph for Kragujevac Tree Networks - Salma Kanwal; Ayesha Riasat; Muhammad Kamran Siddiqui; Shabnam Malik; Khadija Sarwar; Afzal Ammara; Asare-Tuah Anton (Complexity)
Kragujevac tree is indicated by K; K∈Kgq=s2t+1+1,s with order and size s2t+1+1 and s2t+1, respectively. In this paper, we have a look at certain topological features of the total graph and line graph of the total graph of the considered tree, i.e., Kragujevac tree, by computing different topological indices and polynomials.